Operational efficiency of shipping companies: evidence from Malaysia, Singapore, the Philippines, Thailand and Vietnam - Venkadasalam, Saravanan; Mohamad, Azhar; Sifat, Imtiaz Mohammad (Emerald Group Publishing Ltd., 2020)
Purpose: This paper is the first comprehensive investigation of the shipping industry's efficiency in five countries from the ASEAN region: Malaysia, Singapore, the Philippines, Thailand and Vietnam. Design/methodology/approach: Employing Data Envelopment Analysis and Stochastic Frontier Analysis, this paper compares efficiency dynamics of 45 international and offshore shipping providers engaged in fishing and ferrying. Findings: The results indicate consistently diminishing efficiency from 2011 to 2017, a phenomenon that persists even in the traditionally efficient companies. Thereafter, this paper develops Altman Z-scores for the sampled companies and notice that despite rising inefficiency, most firms remain unencumbered by bankruptcy concerns, especially those with large capital buffers. Research limitations/implications: In general, this paper observes a negative relationship between bankruptcy risk and efficiency. Furthermore, the paper notices that reducing inputs does not help boost efficiency. Originality/value: In terms of novel contributions, this paper is the first (to the best of knowledge) to set a Z-score for the ASEAN-based shipping companies. Â© 2020, Emerald Publishing Limited.